Optimal medical treatment and health-related quality of life in patients with chronic systolic heart failure. 3-year follow-up - Szyguła-Jurkiewicz, Bożena; Owczarek, Aleksander; Wojnicz, Romuald; Pudlo, Robert; Schmidt, Barbara; Fryś-Kubala, Magdalena; Klimaszewska, Karolina; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Despite considerable progress in the pharmacological and interventional treatment of chronic heart failure (HF) it still constitutes a significant clinical problem. Aim : The aim of the work was to evaluate HRQoL in patients with HF and optimal medical therapy during 3 years of follow-up. Material and methods : We analysed 197 hospitalised patients with stable systolic HF (NYHA class II and III). Three months prior to hospitalisation the patients were evaluated and received pharmacological recommendations. The therapeutic programme encompassed: maximal tolerated doses of ACEI or ARB, maximal tolerated doses of β-blockers (metoprolol CR or carvedilol), spironolactone, furosemide and digoxin (65% of patients). Inclusion criteria were: stable systolic HF (LVEDd > 57 mm and LVEF 30%) in coronarography, planned heart transplantation and lack of written consent for inclusion into the study. Clinical observation commenced on admission to hospital and lasted 3 years. Results : Men constituted 82.7%. There were 157 patients (77.7%) in NYHA class II, and 40 (20%) in class III. 130 (66%) patients suffered from arterial hypertension. In the 3-year observation period 18.4% of patients died, urgent transplantation was necessary in 3.1%, whilst hospitalisation in 30.1% of patients. In this period we observed a significant improvement within all indexes of HRQoL. Conclusions: Optimal pharmacological treatment and the patients’ co-operation in the therapeutic process brought a significant improvement within HRQoL. The biggest improvement was noted with reference to the RP index (role limitation due to physical health) and MH (mental health).